Novel 6a,12b-Dihydro-6H,7H-chromeno[3,4-c] chromen-6-ones: Synthesis, Structure and Antifungal Activity - Jin-ping Bao; Cui-lian Xu; Guo-yu Yang; Cai-xia Wang; Xin Zheng; Xin-xin Yuan (Molecules, 2019)
A new series of coumarin derivatives, 7-hydroxy-7-(trifluoromethyl)-6a,12b-dihydro-6H,7H-chromeno[3,4-c]chromen-6-ones 3a−p, were synthesized via Michael addition, transesterification and nucleophilic addition from the reaction of 3-trifluoroacetyl coumarins and phenols in the presence of an organic base. The products were characterized by infrared spectroscopy (IR), hydrogen nuclear magnetic resonance spectroscopy (1H-NMR), carbon nuclear magnetic resonance spectroscopy (13C-NMR) and high-resolution mass spectrometer (HRMS). Single crystal X-ray analysis of compounds 3a and 3n clearly confirmed their assigned chemical structures and their twisted conformations. Compound 3a crystallized in the orthorhombic system, Pbca, in which a = 8.6244(2) Å, b = 17.4245(4) Å, c = 22.5188(6) Å, α = 90°, β = 90°, γ = 90°, v = 3384.02(14) Å3, and z = 8. In addition, the mycelial growth rate method was used to examine the in vitro antifungal activities of the title compounds 3a−p against Fusarium graminearum and Fusarium monitiforme at 500 µg/mL. The results showed that compound 3l exhibited significant anti-Fusarium monitiforme activity with inhibitory index of 84.6%.